Copper-fixed quat: a hybrid nanoparticle for application as a locally systemic pesticide (LSP) to manage bacterial spot disease of tomato. Issue 5 (3rd February 2021) - Ozcan, Ali; Young, Mikaeel; Lee, Briana; Liao, Ying-Yu; Da Silva, Susannah; Godden, Dylan; Colee, James; Huang, Ziyang; Mendis, Hajeewaka C.; Campos, Maria G. N.; Jones, Jeffrey B.; Freeman, Joshua H.; et al.
Abstract : A hybrid core–shell silica nanoparticle system integrating Cu nanoclusters and Quat combats resistance development of Xanthomonas perforans responsible for bacterial spot disease of tomatoes. Abstract : The development of bacterial tolerance against pesticides poses a serious threat to the sustainability of food production. Widespread use of copper (Cu)-based products for plant disease management has led to the emergence of copper-tolerant pathogens such as Xanthomonas perforans ( X. perforans ) strains in Florida, which is very destructive to the tomato ( Solanum lycopersicum ) industry. In this study, we report a hybrid nanoparticle (NP)-based system, coined Locally Systemic Pesticide (LSP), which has been designed for improved efficacy compared to conventional Cu-based bactericides against Cu-tolerant X. perforans . The silica core–shell structure of LSP particles makes it possible to host ultra-small Cu NPs (<10 nm) and quaternary ammonium (Quat) molecules on the shell. The morphology, release of Cu and Quat, and subsequent in vitro antimicrobial properties were characterized for LSP NPs with core diameters from 50 to 600 nm. A concentration of 4 μg mL −1 (Cu): 1 μg mL −1 (Quat) was found to be sufficient to inhibit the growth of Cu-tolerant X. perforans compared to 100 μg mL −1 (metallic Cu) required with standard Kocide 3000. Wetting properties of LSP exhibited contact angles below 60°, which constitutes a significant improvement from the 90° and 85° observed with water and Kocide 3000, respectively. The design was also found to provide slow Cu release to the leaves upon water washes, and to mitigate the phytotoxicity of water-soluble Cu and Quat agents. With Cu and Quat bound to the LSP silica core–shell structure, no sign of phytotoxicity was observed even at 1000 μg mL −1 (Cu). In greenhouse and field experiments, LSP formulations significantly reduced the severity of bacterial spot disease compared to the water control. Overall, the study highlights the potential of using LSP particles as a candidate for managing tomato bacterial spot disease and beyond.